You are on page 1of 4

# Tutorial 1 Solutions

## CY1201 (Sem 1 2013/2014)

Standard Problems
Exercise 1. Assume that taxi rate is \$2.50 for the rst kilometre of the trip and 10 cents for each 250 metres more. Dene the price as a function of the distance travelled. SOLUTION . If x is the distance travelled in kilometres, then the price p(x) is p(x) = 2.5, 2.5 + 0.1 if x 1 , if x > 1.

x1 0.25

Here z is the ceiling function, where we round up. That is, z is the least integer greater than or equal to z . You may also choose to use the oor function which rounds down.

Exercise 2. Find the domain of the following functions: (a) f = 3x x3 (b) f = (x 2) SOLUTION . 1+x 1x (a) The expression under the root must be non-negative that is

3x x3 0 , x( 3 0, x)( 3 + x) x 3 or 0 x 3 Thus the answer is (, 3] [0, 3]. (b) First, the denominator cant vanish, so x = 1. Further, the expression under the root must be non-negative, so 1+x 0. 1x A ratio has the same sign as a product, so (1 + x)(1 x) 0. Thus x [1, 1).

Exercise 3. Determine the domain and the range of the following functions: (a) f = 2 + x x2 (b) f = x2 1+x

(c) f = (1)x SOLUTION . (a) The domain is dened by 2 + x x2 0, that is 1 x 2, so it is [1, 2]. Lets nd the range. First of all, notice that f (x) 0. Further, the range consists of all y = f (x) such that the equation 2 + x x2 = y is solvable. Taking the square, we get the quadratic equation x2 x + y 2 2 = 0. It is solvable , so the range is [0, 3/2] while the if and only if 1 4(y 2 2) 0, that is, y 3 2 domain is [1, 2]. (b) Here, the domain is clearly x = 1. The range consists of all y such that the x2 equation f (x) = y is solvable, so 1+ = y , which is x2 yx y = 0. It is solvable x if and only if y 2 + 4y 0, so y 0 or y 4. Thus the domain is R \ {1}, the image is (, 4] [0, +). (c) Clearly, the range consists of just 1 and 1. Further, the expression (1)x does not make sense for irrational x, so the domain contains only rational numbers. Let x = m/n be a fraction in the lowest form. Then (1)x = n (1)m , which is dened whenever m is even or n is odd. Since m/n was supposed to be in the lowest form (so m and n cant be both even), we conclude that n must be always odd. Thus the domain is the set of fractions in the lowest form with odd denominators, and the range is the set of two elements {1, 1}.

Exercise 4. Find the image of the interval (0, 1) if 1 1x (b) f (x) = x x2 (a) f (x) = (c) f (x) = cot x SOLUTION . (a) When x varies from 0 to 1, 1 x varies from 1 to 0 and 1/(1 x) varies from 1 to innity. Thus f (0, 1) = (1, +). 2

(b) The graph of the function g (x) = x x2 is a parabola, the roots are 0 and 1, therefore the maximum value is achieved at x = 1/2 and it equals g (1/2) = 1/2 1/4 = 1/4. Hence g (0, 1) = (0, 1/4]. Since f = g , we have f (0, 1) = (0, 1/2]. (c) When x varies from 0 to 1, x varies from 0 to , so cot x varies from + to . Thus f (0, 1) = R.

Harder Problems
Exercise 5. (a) Suppose that f (x) is increasing and decreasing at the same time. Show that f (x) is constant. (b) Suppose that f (x) is both even and odd at the same time. Show that f (x) is constant zero function, i.e. f (x) = 0 for all x. SOLUTION . (a) Suppose f is increasing and decreasing at the same time. Then we have x y = f (x) f (y ), and x y = f (x) f (y ). Hence the two equations above says that for any two numbers x y , we have f (x) = f (y ). Since we can swap the x, y around, this says that for any two numbers x, y , we have f (x) = f (y ). Now let C = f (0). Then for any x R, by applying the above (with y = 0), we get f (x) = f (0) = C . Thus f is the constant function f (x) = C . (b) Suppose that f is both even and odd. Now since f (x) is even we have f (x) = f (x) for every x. Since f (x) is odd we get f (x) = f (x) for every x. Combining both facts, we get f (x) = f (x) = f (x) for every x. This means that f (x) = f (x) and so 2f (x) = 0 and therefore f (x) = 0 for every x. Therefore, f (x) is the constant zero function.

Exercise 6. (a) Prove that any function f : R R can be written as the sum of an even function and an odd function. That is, nd an even function g (x) and an odd function h(x) such that f (x) = g (x) + h(x). (b) Prove that this expression is unique.

SOLUTION . (a) Given a function f . Let f (x) + f (x) 2 f (x) f (x) h(x) = 2 g ( x) = Then g (x) is even, because g (x) = f (x) + f ((x)) f (x) + f (x) = = g (x), 2 2

and h(x) is odd, because h(x) = Furthermore, g (x) + h(x) = f (x) + f (x) f (x) f (x) + = f ( x) 2 2 f (x) f ((x)) f (x) f (x) = = h(x). 2 2

(b) To show that this expression f (x) = g (x) + h(x) is unique, we need to show that every time we write f (x) = E (x)+ O(x) for any even function E (x) and odd function O(x), we must have E (x) = g (x) and O(x) = h(x). Now x any even E (x) and any odd O(x) such that f (x) = E (x) + O(x). Since E (x) is even, and E (x) = f (x) O(x), we have E (x) = E (x) f (x) O(x) = f (x) O(x) f (x) + O(x) = f (x) O(x) [Since O(x) is odd] 2O(x) = f (x) f (x) f (x) f (x) O(x) = = h(x) 2 Similarly now starting with O(x) = O(x), we have O(x) = O(x) f (x) E (x) = (f (x) E (x)) f (x) E (x) = f (x) + E (x) [Since E (x) is odd] 2E (x) = f (x) + f (x) f (x) + f (x) E (x) = = g ( x) 2